Oxide material and preparation method thereof, positive electrode sheet and lithium ion battery

By directly sintering or low-temperature sintering lithium-containing materials, the problems of batching ratio error and uneven mixing in the preparation of nickel-cobalt-manganese oxide materials are solved, and high consistency of the material and excellent battery performance are achieved.

CN119764438APending Publication Date: 2025-04-04PINNACLE MATERIAL TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411939865.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the preparation process of nickel-cobalt lithium manganate materials in the prior art, problems of batching ratio errors and uneven mixing are prone to occur, resulting in poor product consistency and poor electrical performance.

Method used

By directly sintering or sintering lithium-containing materials at low temperatures, the lithium ion diffusion resistance is reduced and the structural stability and consistency of the material are improved.

Benefits of technology

Improves the consistency of oxide materials and battery performance, reduces production costs and energy consumption, and enhances rate performance and high-temperature storage capabilities.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119764438A_ABST
    Figure CN119764438A_ABST
Patent Text Reader

Abstract

The present invention provides an oxide material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. The chemical formula of the oxide material is Li m Ni x Co y Mn z A (1‑x‑y‑z) O2; wherein, 0.9≤m≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0<x+y+z≤1, and A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn. The present invention achieves atomic-level mixing of lithium with nickel, cobalt, and manganese elements to improve the mass transfer path during solid-phase reaction, and the oxide can be synthesized at a relatively low temperature, thereby saving manufacturing costs and improving the consistency of product batches. The lithium element and nickel, cobalt, and manganese elements are evenly distributed in the oxide material of the present invention, and the structure is stable. As a positive electrode material, it has good rate performance in a high limiting voltage system, and excellent high-temperature cycling and storage performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion batteries, and in particular relates to an oxide material and a preparation method thereof, a positive electrode sheet and a lithium ion battery. Background Art

[0002] In the prior art, lithium nickel-cobalt-manganese oxide is generally prepared by mixing a nickel-cobalt-manganese precursor raw material and a lithium source raw material in a certain proportion and then sintering them at high temperature. In this process, batching and mixing operations are required. Batching is a key link in the traditional production process of nickel cobalt manganese oxide materials. It requires that each raw material has an independent quantitative value and that the ratio between the raw materials put into it must be correct. In the batching process, due to the hygroscopicity of the powder, the operation of personnel or the fluctuation of equipment, it is easy to produce errors in the batching ratio, which reduces the consistency of the batch and even affects the electrical properties of the nickel cobalt manganese oxide. In the mixing process, due to the large difference in density between the lithium source and the nickel cobalt manganese precursor raw material, stratification is easy to occur in the solid phase mixing, resulting in uneven mixing and poor consistency of the product nickel cobalt manganese oxide. In the high-temperature sintering process, the solid phase diffusion rate of lithium ions at the interface between the nickel cobalt manganese precursor raw material and the lithium source is slow, which makes it difficult for the lithium ions in the lithium source to diffuse and migrate into the particles of the nickel cobalt manganese precursor raw material, resulting in inconsistent lithium ion concentrations on the surface and inside of the particles, and even causing lithium deficiency in the core of the particles, and the prepared lithium cobalt manganese oxide has poor rate performance.

[0003] Therefore, a new technical method is developed to solve the above-mentioned problems. Summary of the invention

[0004] The purpose of the present invention is to provide an oxide material and a preparation method thereof, wherein the lithium-containing material is directly sintered or the lithium-containing material is mixed with an appropriate amount of lithium source and then sintered to obtain the oxide material. The material preparation process is simple and easy, and effectively reduces the problem of poor material battery performance caused by the large diffusion resistance and slow diffusion rate of lithium ions from the surface of the precursor to the inside, while improving the consistency of the oxide material.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions:

[0006] An oxide material, the chemical formula of the oxide material is Li m Ni a Co b Mn c A (1-a-b-c) O2; wherein, 0.9≤m≤1.3, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤a+b+c≤1, and A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn.

[0007] The mass fraction of lithium element in the oxide material is 6.45% to 9.36%, and the total mass fraction of nickel element, cobalt element and manganese element is 50% to 60%.

[0008] The D50 median particle size of the oxide material is 1.5-20 μm, and the BET is 0.2-1.8 m2 / g. Preferably, the D50 median particle size is 2.0-18 μm, and the BET is 0.4-1.0 m2 / g.

[0009] The present invention also provides a method for preparing the above oxide material, wherein the oxide material can be directly sintered from a lithium-containing material or sintered after mixing the lithium-containing material with an appropriate amount of lithium source. The lithium-containing material can be prepared by a solid phase method, a liquid phase method or a solid-liquid mixing method. The liquid phase method or the solid-liquid mixing method is preferred. The lithium content in the lithium-containing material can be controlled.

[0010] The sintering temperature is 500-1000°C, the heating rate is 1-8°C / min, the sintering time is 5-20 hours, the gas introduced is oxygen-containing air, the partial pressure of oxygen is ≥0.21atm, and the gas flow rate is 100-700Nm 3 Preferably, the sintering temperature is 500-960°C, and the heating rate is 1-6°C / min.

[0011] The lithium-containing material provided by the present invention has the following characteristics: n Ni x Co y Mn z A (1-x-y-z) P, P is CO3 2- 、C2O4 2- , O 2- 、CH3COO - One or more of the following. Wherein, 0.1≤n≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0<x+y+z≤1, and A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn.

[0012] The mass fraction of Li element in the lithium-containing material is 0.5% to 8.4%, the mass fraction of (Ni+Co+Mn+A) is 21% to 61%, and the mass fraction of P is 38% to 74%.

[0013] The median particle size of D50 of the lithium-containing material is 1.5 to 25 μm. Preferably, the median particle size of D50 is 1.5 to 25 μm

[0014] The lithium-containing material is heated at 500-600°C in an oxygen-containing atmosphere (oxygen partial pressure ≥ 0.21 atm) with a gas flow rate of 100-700 Nm 3 / h, sintered for 2 to 10 hours, and in the XRD spectrum of the obtained product under the test conditions of Cu target Kα1, scanning rate 4° / min, and 2θ range of 10 to 80°, the half-peak width of the diffraction peak 18.5-19.0° is 0.100 to 0.380.

[0015] The DSC spectrum of the lithium-containing material has at least two endothermic peaks between 100° C. and 350° C.

[0016] Preferably, a method for preparing a lithium-containing material comprises the following steps:

[0017] ① Homogenize and mix the Li source, Ni source, Co source, Mn source and A source in a molar ratio of Li:Ni:Co:Mn:A=n:x:y:z:(1-xyz) to obtain a mixed material; wherein 0.1≤m≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z≤1; the homogenize and mix the mixed material including at least one of mechanical stirring, shearing, shaking, crushing and emulsification. Add an organic polyacid to the mixed material obtained in step ① for dispersion.

[0018] ② Drying the obtained mixture to obtain a lithium-containing material.

[0019] Or including the following steps:

[0020] ① Raw material preparation: Soluble salts of Li, Ni, Co, Mn and A elements are prepared in the molar ratio of Li:

[0021] Ni: Co: Mn: A = n: x: y: z: (1-xyz) is prepared into a mixed solution with a metal ion concentration of 1 to 4 mol / L; a precipitant is prepared into a solution with a concentration of 1 to 5 mol / L; a pH regulator is prepared into a solution with a concentration of 2 to 8 mol / L; a polymer surfactant is prepared into a solution with a concentration of 0.1 to 10 g / L;

[0022] ② Feeding reaction: Add the polymer surfactant solution to the reactor containing deionized water, stir at a stirring speed of 500-1500 rpm for 20-80 minutes, and then use a metering pump to pump at a speed of 2-50 ml / min.

[0023] The transition metal soluble salt solution and the precipitant solution are added simultaneously at a material flow rate;

[0024] ③ Aging and washing of slurry: After the addition of step ② is completed, add pH regulator solution at a feed rate of 5-50 ml / min using a metering pump to adjust the pH value to 7-10, discharge after aging for 5-15 hours, and wash

[0025] Filtering;

[0026] ④ Drying: Dry the filtered product obtained in step ③ to obtain a lithium-containing material.

[0027] Preferably, the soluble salt of the elements Li, Ni, Co, Mn and A is at least one of sulfate and nitrate.

[0028] Preferably, the raw materials of the Li, Ni, Co, Mn and A elements may be at least one of carbonate, oxalate, chloride, hydroxide, citrate and oxide.

[0029] Preferably, the Li source includes at least one of lithium hydroxide monohydrate, lithium carbonate, lithium acetate, lithium fluoride, and lithium citrate.

[0030] Preferably, the Ni source, Co source, Mn source and A source are at least one of carbonate, oxide and acetate.

[0031] Preferably, the precipitant is at least one of ammonium carbonate, oxalic acid, sodium carbonate and ammonium bicarbonate.

[0032] Preferably, the pH adjuster is at least one of sodium hydroxide, potassium hydroxide, ammonia water, sodium carbonate and sodium bicarbonate.

[0033] Preferably, the organic polyacid is at least one of polyacrylic acid, polyacrylic acid copolymer, polyvinyl alcohol, citric acid, acrylic acid, and oxalic acid.

[0034] Preferably, the dispersing aid may be polyvinyl alcohol, lithium dodecyl sulfate, Tween-80, lithium stearate, octylphenol polyoxyethylene ether, etc.

[0035] Preferably, the Li source includes at least one of lithium oxalate, lithium carbonate, lithium acetate, lithium fluoride, lithium chloride, lithium tert-butoxide and lithium citrate.

[0036] Preferably, the organic polyacid is at least one of polyacrylic acid, polyacrylic acid copolymer, polyvinyl alcohol, citric acid, acrylic acid, and oxalic acid.

[0037] Preferably, the mass fraction of the organic polyacid in the total mass of the raw materials is 1.0%-5.0%.

[0038] The present invention also provides a positive electrode sheet, comprising the above oxide material. The compaction density of the positive electrode sheet is 3.2-4.2 g / cc.

[0039] The present invention also provides a lithium ion battery, comprising the above-mentioned positive electrode sheet. The prepared lithium ion battery has a 0.2C capacity of 140 mAh / g to 220 mAh / g in the cut-off voltage range of 4.2 to 4.6 V. Its 2C / 0.2C rate performance is ≥90%. The high temperature storage battery cell swelling rate is ≤5%.

[0040] Compared with the prior art, the present invention has at least the following beneficial effects:

[0041] (1) Compared with traditional positive electrode materials, the oxide material of the present invention is prepared from a lithium-containing material through a thermal sintering reaction. In the lithium-containing material, lithium is mixed with nickel, cobalt, manganese, etc. at the atomic level, which reduces the batching process, improves the consistency of product batches, production efficiency and saves costs.

[0042] (2) Compared with traditional positive electrode materials, the oxide material of the present invention can be directly prepared from lithium-containing materials at a lower temperature, thus saving energy.

[0043] (3) Compared with traditional positive electrode materials, the oxide material of the present invention improves the structural stability of the oxide material by uniformly distributing the lithium element and the nickel, cobalt and manganese elements in the lithium-containing material. In a high limiting voltage system, the oxide material has good rate performance, and excellent high-temperature storage and cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 XRD diagrams of Example 1 of the present invention and Comparative Example 1 at different sintering temperatures;

[0045] Figure 2 This is a SEM image of the lithium-containing material of Example 1 of the present invention when the sintering temperature is 550° C.;

[0046] Figure 3 This is a SEM image of the lithium-containing material of Example 1 of the present invention when the sintering temperature is 920° C.;

[0047] Figure 4 This is a SEM image of the precursor of Comparative Example 1 of the present invention after being mixed with lithium at a sintering temperature of 550° C.;

[0048] Figure 5 This is a SEM image of the precursor of Comparative Example 1 of the present invention after being mixed with lithium at a sintering temperature of 950° C.;

[0049] Figure 6 The DSC curves of Example 1 and Comparative Example 1 of the present invention are shown in FIG.

[0050] Figure 7 The charge and discharge curves of Example 1 of the present invention and Comparative Example 1 at 4.4V 0.1C are shown;

[0051] Figure 8 Graph showing the number of cycles and capacity retention at 4.5V 45°C 1C / 1C for Example 1 of the present invention and Comparative Example 1. DETAILED DESCRIPTION

[0052] In order to make the technical solutions and advantages of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0053] In a first aspect of the present invention, the present invention provides an oxide material having a chemical formula of Li m Ni a Co b Mn c A (1-a-b-c) O2; wherein, 0.9≤m≤1.3, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0≤a+b+c≤1, and A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn.

[0054] The oxide material of the present invention requires a low sintering temperature, a short sintering time, a simple process, and low energy consumption. The oxide material is applied at a cut-off voltage of 4.2-4.6V, has good rate performance, and a small swelling rate of a high-temperature storage cell.

[0055] In one embodiment of the present invention, the mass fraction of lithium element in the oxide material is 6.45% to 9.36%, specifically 6.45%, 6.5%, 6.6%, 6.7%, 6.8%, 6.9%, 7.0%, 7.1%, 7.2%, 7.3%, 7.4%, 7.5%, 7.7%, 7.8%, 7.9%, 8.0%, 8.2%, 8.5%, 8.7%, 8.9%, 9.1%, 9.2%, 9.3%, 9.32%, and 9.36%; when the mass fraction of lithium element is controlled within the above range, it can ensure that sufficient lithium ions participate in the solid phase reaction during the sintering process and generate a complete crystalline phase structure.

[0056] In one embodiment of the present invention, the total mass fraction of nickel, cobalt and manganese in the oxide material is 50% to 60%, specifically 50%, 52%, 55%, 58%, 59% and 60%. When the total mass fraction of the above elements is controlled within the above range, nickel, cobalt and manganese cooperate to form a stable two-dimensional layered structure. Among them, the cobalt element can improve the electronic conductivity of the material, the manganese element can provide a stable structural skeleton, improve the cycle performance and storage performance; the nickel element provides capacity performance by providing redox reaction.

[0057] In one embodiment of the present invention, the D50 median particle size of the oxide material is 1.5 to 20 μm, specifically 1.5 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, 19 μm, 20 μm. The compaction density of the manufactured pole piece can be adjusted by using different median particle sizes.

[0058] According to the second aspect of the present invention, the present invention also provides a method for preparing the above oxide material, which comprises directly sintering the lithium-containing material or mixing the lithium-containing material with an appropriate amount of lithium source and then sintering, the sintering temperature is 500-1000°C, the heating rate is 1-8°C / min, the sintering time is 5-20 hours, the gas introduced is oxygen-containing air, the partial pressure of oxygen is ≥0.21atm, and the gas flow rate is 100-700Nm 3 Preferably, the sintering temperature is 500-960°C, and the heating rate is 1-6°C / min.

[0059] According to a third aspect of the present invention, the present invention provides a lithium-containing material, whose chemical formula is: Li n Ni x Co y Mn z A (1-x-y-z) P, P can be one or more of carbonate, oxalate, hydroxide, acetate, oxygen anion. Wherein, 0.1≤n≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0<x+y+z≤1, A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, Zn. Wherein the mass fraction of Li element is 0.5% to 8.4%, the mass fraction of (Ni+Co+Mn+A) is 21% to 61%, and the mass fraction of P is 38% to 74%. The median particle size of D50 of the lithium-containing material is 1.5 to 25 μm. The DSC spectrum of the lithium-containing material has at least two endothermic peaks between 100°C and 350°C.

[0060] In one embodiment of the present invention, the lithium-containing material is prepared by a solid-liquid mixing method, which includes the following steps:

[0061] (1) A Li source, a Ni source, a Co source, a Mn source and an A source are homogenously mixed in a molar ratio of Li:Ni:Co:Mn:A=n:x:y:z:(1-xyz) to obtain a mixed material; wherein 0.1≤n≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0≤x+y+z≤1; the homogenous mixing includes at least one of mechanical stirring, shearing, shaking, crushing and emulsification. An organic polyacid is added during the homogenous mixing process to improve dispersibility.

[0062] (2) Adding an organic polyacid to the mixed material obtained in step ① to disperse it, and washing and drying it to obtain a lithium-containing material.

[0063] In the embodiment of the present invention, Ni ions, Co ions, Mn ions, Li ions and A element are mixed with organic polyacid as a medium, and the uniformity of mixing between the elements is further enhanced through homogeneous mixing.

[0064] In one embodiment of the present invention, the Li source includes at least one of lithium hydroxide monohydrate, lithium oxalate, lithium carbonate, lithium nitrate, lithium acetate, lithium fluoride, lithium chloride, lithium tert-butoxide and lithium citrate.

[0065] In one embodiment of the present invention, the Ni source, the Co source, the Mn source and the A source are at least one of carbonate, sulfate, oxide, acetate, oxalate and hydroxide;

[0066] In one embodiment of the present invention, the organic polyacid is at least one of polyacrylic acid, polyacrylic acid copolymer, polyvinyl alcohol, citric acid, acrylic acid, and oxalic acid.

[0067] In one embodiment of the present invention, the mass fraction of the organic acid is 1.0%-5.0% of the total mass fraction, specifically 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.7%, 1.8%, 1.9%, 2.0%, 2.10%, 2.2%, 2.5%, 3.0%, 3.5%, 4.0%, 4.2%, 4.5%, 4.8%, 5.0%. When the mass fraction of the organic acid is controlled within the above range, the mixture can be dispersed more evenly and the use of the organic acid can be moderate.

[0068] In one embodiment of the present invention, the equipment for homogeneous mixing includes a high-speed disperser, a ball mill, a high-speed wall breaking machine, a homogenizer, etc.

[0069] In one embodiment of the present invention, the lithium-containing material is prepared by a liquid phase method, which includes the following steps: (1) raw material preparation: preparing soluble salts of Li, Ni, Co, Mn, and A elements according to the molar ratio of Li: Ni: Co: Mn: A = n: x: y: z: (1-xyz) into a mixed solution with a metal ion concentration of 1 to 4 mol / L; preparing a precipitant into a solution with a concentration of 1 to 5 mol / L; preparing a pH regulator into a solution with a concentration of 2 to 8 mol / L; preparing a dispersant into a solution with a concentration of 0.1 to 10 g / L;

[0070] (2) Feeding reaction: Add the polymer surfactant solution to a reaction kettle containing deionized water, stir at a stirring speed of 500 to 1500 rpm for 20 to 80 min, and then use a metering pump to simultaneously add the transition metal soluble salt solution and the precipitant solution at a feed flow rate of 2 to 50 ml / min;

[0071] (3) Aging and washing of the slurry: After the addition is completed, a pH adjusting agent solution is added at a feed flow rate of 5 to 50 ml / min using a metering pump to adjust the pH value to 7 to 10. After aging for 5 to 15 hours, the slurry is discharged and washed, filtered and dried.

[0072] In one embodiment of the present invention, the solute of the metal salt solution used is one or more of sulfates, chlorides, nitrates and acetates of elements such as lithium, cobalt, nickel, manganese, and A. In one embodiment of the present invention, the precipitant used can be one or more of carbonates, hydroxides, oxalates, citrates, and bicarbonates of lithium, sodium, calcium, and potassium.

[0073] In one embodiment of the present invention, the dispersant used may be one or more of fatty alcohol polyoxyethylene ether, fatty acid polyoxyethylene ester, alkyl polysaccharide, alkyl alcohol amide, polyacrylamide, and ethoxylated sorbitan fatty acid ester.

[0074] In one embodiment of the present invention, the heating rate of the sintering process is 1-6°C / min; the heating temperature is 500-960°C, specifically 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 920°C, 950°C, 960°C; the sintering time is 5-20h, specifically 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, 17h, 18h, 19h, 20h.

[0075] In one embodiment of the present invention, the gas introduced into the sintering process is an oxygen-containing gas, the partial pressure of oxygen in the oxygen-containing gas is ≥ 0.21atm, specifically 0.21atm, 0.30atm, 0.40atm, 0.50atm, 0.60atm, 0.70atm, 0.80atm, 0.90atm, 0.97atm%, and the atmosphere flow rate is 100-700Nm 3 / h, specifically 100Nm 3 / h、200Nm 3 / h、300Nm 3 / h、400Nm 3 / h、500Nm 3 / h、600Nm 3 / h、700Nm 3 / h.

[0076] According to a fourth aspect of the present invention, the present invention further provides a positive electrode sheet comprising the above-mentioned oxide material.

[0077] The positive electrode sheet can be made by the following method: the above-mentioned oxide material, conductive agent, binder and N-methylpyrrolidone are uniformly mixed in a mass ratio of 100:2.1:1:20-32 to obtain a positive electrode slurry; the slurry is uniformly coated on the positive electrode current collector, and the positive electrode sheet is obtained after drying, winding and rolling. The coating surface density of a single side of the positive electrode sheet is 15-20 mg / cm 2 The conductive agent may include but is not limited to at least one of conductive carbon black, conductive graphite, carbon fiber, carbon nanotube and graphene, and the binder may include but is not limited to at least one of polyvinylidene fluoride, styrene-butadiene rubber and carboxymethyl cellulose.

[0078] The obtained positive electrode sheet was subjected to a compaction density test, and the compaction density was 3.2-4.2 g / cc. (After rolling the weighed electrode sheet, fold the electrode sheet in half twice to confirm that the electrode sheet does not leak light as the rolling limit, and measure the length, width, and thickness of the electrode sheet under this condition; the compaction density of the electrode sheet is calculated according to the formula electrode sheet compaction density = (electrode sheet weight-foil material weight) / (electrode sheet thickness-foil material thickness).

[0079] According to a fifth aspect of the present invention, the present invention further provides a lithium-ion battery comprising the above-mentioned positive electrode sheet.

[0080] The lithium ion battery further comprises a separator, which can be selected from various separators used in lithium ion batteries known to those skilled in the art, such as polypropylene microporous membrane, polyethylene felt, glass fiber felt or ultrafine glass fiber paper.

[0081] The lithium ion battery also includes an electrolyte, which can be various conventional electrolytes, such as non-aqueous electrolytes. The non-aqueous electrolyte is a solution formed by an electrolyte lithium salt in a non-aqueous solvent, and conventional non-aqueous electrolytes known to those skilled in the art can be used. For example, the electrolyte can be selected from at least one of lithium hexafluorophosphate (LiPF6), lithium perchlorate (LiClO4), lithium tetrafluoroborate (LiBF4), lithium hexafluoroarsenate (LiAsF6) and lithium hexafluorosilicate (LiSiF6). The non-aqueous solvent can be selected from a mixed solution of a chain acid ester and a cyclic acid ester, wherein the chain acid ester can be at least one of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), methyl propyl carbonate (MPC) and dipropyl carbonate (DPC). The cyclic acid ester can be at least one of ethylene carbonate (EC), propylene carbonate (PC) and vinylene carbonate (VC).

[0082] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material used in the negative electrode active material layer may include but is not limited to one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, etc. The graphite may be selected from one or more of artificial graphite, natural graphite and modified graphite; the silicon-based material may be selected from one or more of elemental silicon, silicon oxide compounds, silicon-carbon composites, and silicon alloys; the tin-based material may be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector may be copper foil, PET copper foil or aluminum foil.

[0083] The present invention will be further described below by means of specific examples.

[0084] Example 1

[0085] This embodiment provides an oxide LiNi 0.49 Co 0.2 Mn 0.3 La 0.01 O2, the preparation steps include:

[0086] S1: According to the molar ratio of Li:Ni:Co:Mn:La=1.03:0.49:0.2:0.3:0.01, 52.5 g of lithium oxalate (Li2C2O4), 71.9 g of nickel oxalate (NiC2O4), 35.4 g of cobalt acetate (Co(CH3COO)2), 42.9 g of manganese oxalate (MnC2O4), and 3.16 g of lanthanum acetate (La(CH3COO)3) were weighed and mechanically mixed to obtain a mixture;

[0087] S2: Weigh 1.5% citric acid (10.2 g) and perform high shear dispersion. The dispersed slurry is placed in an oven for drying at 120°C for 5 hours to obtain a lithium-containing material Li 1.03 Ni 49 Co 0.2 Mn 0.3 La 0.01 (C2O4) 1.29 (CH3COO) 0.43 ;

[0088] S3: The lithium-containing material is placed in a sagger in a muffle furnace under an oxygen-containing air atmosphere with an oxygen partial pressure of 0.35 atm and a gas flow rate of 350 Nm 3 / h, firstly heat to 300℃ at a rate of 6℃ / min, keep warm for 2h; then heat to 550℃ at a rate of 6℃ / min, keep warm for 8h, take samples for testing, then heat to 920℃ at a rate of 6℃ / min, keep warm for 8h, complete sintering; after cooling to room temperature with the furnace, grind or crush the obtained material to D50 of 4.5μm to obtain LiNi oxide 0.49 Co 0.2 Mn 0.3 La 0.01 O2.

[0089] Example 2

[0090] This embodiment provides an oxide Li 1.02 Ni 0.49 Co 0.2 Mn 0.3 La 0.01 O2, the preparation steps include:

[0091] S1: According to the molar ratio of Li:Ni:Co:Mn:La=0.3:0.49:0.2:0.3:0.01, 15.3 g of lithium oxalate (Li2C2O4), 71.9 g of nickel oxalate (NiC2O4), 35.4 g of cobalt acetate (Co(CH3COO)2), 42.9 g of manganese oxalate (MnC2O4), and 3.16 g of lanthanum acetate (La(CH3COO)3) were weighed and homogenized to obtain an emulsion;

[0092] S2: The obtained emulsion was introduced into a spray dryer (model L-317). The feed temperature was set to 50°C, the feed rate was 10 ml / min, the air volume was 900 L / h, and the air temperature was 185°C. The lithium-containing material Li was collected from the discharge port. 0.3 Ni 49 Co 0.2 Mn 0.3 La 0.01 (C2O4) 1.29 (CH3COO) 0.43 .

[0093] S3: Add 27.71g of lithium carbonate (Li2CO3) to the lithium-containing material and mix them evenly. Put them into a sagger and place them in a muffle furnace. Under the condition of oxygen-containing air atmosphere, the oxygen partial pressure is 0.35atm and the gas flow rate is 350Nm 3 / h, firstly heat to 300℃ at a rate of 6℃ / min, keep warm for 2h; then heat to 550℃ at a rate of 6℃ / min, keep warm for 2h, then heat to 750℃ at a rate of 6℃ / min, keep warm for 2h, then heat to 920℃ at a rate of 4℃ / min, keep warm for 10h, complete sintering, and after cooling to room temperature with the furnace, grind or crush the obtained material to D50 of 5.5μm to obtain oxide Li 1.02 Ni 0.49 Co 0.2 Mn 0.3 La 0.01 O2.

[0094] Example 3

[0095] This embodiment provides an oxide Li 1.02 Ni 0.49 Co 0.2 Mn 0.3 La 0.01 O2, the preparation steps include:

[0096] S1: Prepare 10L of a mixed aqueous solution of 4.9M nickel sulfate (NiSO4), 2.0M cobalt sulfate (CoSO4), 3.0M manganese sulfate (MnSO4), 0.1M lanthanum acetate (La(CH3COO)3) and 5.25M lithium sulfate (Li2SO4), i.e. weigh 1299.2g NiSO4·6H2O, 566.2g CoSO4·7H2O, 508.7g MnSO4·H2O, 31.6g La(CH3COO)3 and 577.2g Li2SO4 were dissolved in 3000g deionized water at about 50℃ and the volume was adjusted to 10L; 10L of 15.25M sodium carbonate solution was prepared by weighing 1616.5g Na2CO3 and dissolving it in 8000g deionized water at about 50℃ and the volume was adjusted to 10L; 2L of 10M ammonia solution was prepared by weighing 70 0g of 25% ammonia solution, fixed to 2L; weigh 2g of high molecular surfactant polyethylene glycol, dissolve it in 3L of deionized water and add it to the reactor, stir it at a stirring speed of 800rpm for 40min; use a peristaltic pump to simultaneously add a mixed solution of nickel sulfate, cobalt sulfate, manganese sulfate and lithium sulfate with a metal ion concentration of 2mol / L and a sodium carbonate solution with a concentration of 1.5mol / L at a feeding rate of 10ml / min, feed for 8.4h, after the feeding is completed, use a peristaltic pump to add 5mol / L ammonia solution at 20ml / min, adjust the pH value to the specified value of 8, keep the stirring speed unchanged at 800rpm, after aging for 7h, the slurry is centrifuged and filtered by a centrifuge (model YLT-1200) to obtain a filter cake; the filter cake is placed in an electric hot air dryer (model 101-0ABS) and dried at a constant temperature of 80°C for 3h, and then taken out to obtain a lithium-containing material Li1.05 Ni 0.49 Co 0.2 Mn 0.3 La 0.01 (CO3) 1.5 .

[0097] S2: The lithium-containing material is placed in a sagger in a muffle furnace under an oxygen-containing atmosphere with an oxygen partial pressure of 0.75 atm and a gas flow rate of 550 Nm 3 / h, firstly, the temperature was raised to 300℃ at a rate of 6℃ / min and kept at that temperature for 2h; then the temperature was raised to 920℃ at a rate of 6℃ / min and kept at that temperature for 8h to complete the sintering; after cooling to room temperature with the furnace, the obtained material was ground or crushed to a D50 of 4.8μm to obtain the oxide Li 1.02 Ni 0.49 Co 0.2 Mn 0.3 La 0.01 O2.

[0098] Example 4

[0099] This embodiment provides an oxide LiNi 0.7 Co 0.1 Mn 0.18 Y 0.02 O2, except that the raw materials are weighed according to the element molar ratio, the rest of the preparation steps are similar to those of Example 1, the main difference is that acrylic acid is added in an amount of 2.5g to obtain the lithium-containing material Li 1.03 Ni 0.7 Co 0.1 Mn 0.18 Y 0.02 (C2O4) 1.38 (CH3COO) 0.26 .

[0100] During the sintering stage of the positive electrode material, the lithium-containing material is placed in a sagger in a muffle furnace under an oxygen-containing atmosphere with an oxygen partial pressure of 0.70 atm and a gas flow rate of 550 Nm 3 / h, firstly, the temperature was raised to 300℃ at a rate of 6℃ / min and kept at that temperature for 2h; then the temperature was raised to 800℃ at a rate of 6℃ / min and kept at that temperature for 8h to complete the sintering; after cooling to room temperature with the furnace, the obtained material was ground or crushed to a D50 of 5.2μm to obtain the oxide LiNi 0.7 Co 0.1 Mn 0.18 Y 0.02 O2.

[0101] Example 5

[0102] This embodiment provides an oxide LiNi 0.6 Co0.15 Mn 0.15 Ti 0.1 O2, the main preparation steps are the same as those in Example 2. The difference is that according to the molar ratio of Li: Ni: Co: Mn: La = 1.03: 0.6: 0.15: 0.15: 0.1, 52.48g of lithium oxalate (Li2C2O4), 106.1g of nickel acetate (Ni(CH3COO)2), 21.9g of cobalt oxalate (CoC2O4), 21.3g of manganese oxalate (MnC2O4), 8.0g of titanium dioxide (TiO2) are weighed, and 1.8% of polyvinyl alcohol (15.6g) is weighed during emulsification and mixing to obtain the lithium-containing material Li 1.03 Ni 0.6 Co 0.15 Mn 0.15 Ti 0.1 (C2O4) 0.8 (CH3COO) 1.2 (O2) 0.1 .

[0103] S3: The lithium-containing material is placed in a sagger and placed in a muffle furnace under an oxygen-containing atmosphere with an oxygen partial pressure of 0.55 atm and a gas flow rate of 550 Nm 3 / h, firstly, the temperature was raised to 300℃ at a rate of 6℃ / min and kept at that temperature for 2h; then the temperature was raised to 830℃ at a rate of 6℃ / min and kept at that temperature for 8h to complete the sintering; after cooling to room temperature with the furnace, the obtained material was ground or crushed to a D50 of 4.8μm to obtain the oxide LiNi 0.6 Co 0.15 Mn 0.15 Ti 0.1 O2.

[0104] Example 6

[0105] Providing an oxide Li 1.02 Ni 0.8 Co 0.05 Mn 0.05 Al 0.1 The main process is similar to that of Example 3.

[0106] S1: Prepare 5L of a mixed aqueous solution of 8M nickel sulfate (NiSO4), 0.5M cobalt sulfate (CoSO4), 0.5M manganese sulfate (MnSO4), 1M aluminum sulfate (Al2(SO4)3) and 5.25M lithium sulfate (Li2SO4), i.e. weigh 2112.2g NiSO4·6H2O, 141.5g CoSO4·7H2O, 127.2g MnSO 4·H2O, 342.2g Al2(SO4)3 and 577.2g Li2SO4, dissolve them in 6000g deionized water at about 50℃, and adjust the volume to 10L; prepare 10L of 20M oxalic acid solution, that is, weigh 2521.4g H2C2O4·2H2O, dissolve it in 8000g deionized water at about 50℃, and adjust the volume to 5L; prepare 2L of 10M ammonia solution, that is, weigh 700g 25% ammonia solution, fixed to 2L; weigh 2g of high molecular surfactant polyethylene glycol, dissolve it in 3L of deionized water and add it to the reactor, stir it at a stirring speed of 800rpm for 40min; use a peristaltic pump to simultaneously add a mixed solution of nickel sulfate, cobalt sulfate, manganese sulfate and lithium sulfate with a metal ion concentration of 2mol / L and an oxalic acid solution with a concentration of 2mol / L at a feeding rate of 10ml / min, feed for 8.4h, after the feeding is completed, use a peristaltic pump to add 5mol / L ammonia solution at 20ml / min, adjust the pH value to the specified value of 8, keep the stirring speed unchanged at 800rpm, after aging for 7h, the slurry is centrifuged and filtered by a centrifuge (model YLT-1200) to obtain a filter cake; the filter cake is placed in an electric hot air dryer (model 101-0ABS) and dried at a constant temperature of 80℃ for 3h, and then taken out to obtain a lithium-containing material Li 1.05 Ni 0.8 Co 0.05 Mn 0.05 Al 0.1 (C2O4) 1.55 .

[0107] S2: The lithium-containing material is placed in a sagger in a muffle furnace under an oxygen-containing atmosphere with an oxygen partial pressure of 0.85 atm and a gas flow rate of 550 Nm 3 / h, firstly, the temperature was raised to 300℃ at a rate of 6℃ / min and kept at that temperature for 2h; then, the temperature was raised to 720℃ at a rate of 6℃ / min and kept at that temperature for 8h to complete the sintering; after cooling to room temperature with the furnace, the obtained material was ground or crushed to a D50 of 5.2μm to obtain the oxide Li 1.02 Ni 0.8 Co 0.05 Mn 0.05 Al 0.1 O2.

[0108] Example 7

[0109] This embodiment provides an oxide Li 1.3 Ni 0.5 Co 0.2 Mn 0.25 Sb 0.05 O2, the preparation steps include:

[0110] S1: According to the molar ratio of Li:Ni:Co:Mn:La=1.32:0.5:0.2:0.25:0.05, 67.3 g of lithium oxalate (Li2C2O4), 73.4 g of nickel oxalate (NiC2O4), 35.4 g of cobalt acetate (Co(CH3COO)2), 35.7 g of manganese oxalate (MnC2O4), and 7.3 g of antimony trioxide (Sb2O3) were weighed and homogenized to obtain an emulsion;

[0111] S2: The obtained emulsion was introduced into a spray dryer (model L-317). The feed temperature was set to 50°C, the feed rate to 10 ml / min, the air volume to 900 L / h, and the air temperature to 185°C. The lithium-containing material Li was collected from the discharge port. 1.32 Ni 0.5 Co 0.2 Mn 0.25 Sb 0.05 (C2O4) 1.4 (CH3COO) 0.4 (O2) 0.075 .

[0112] S3: The lithium-containing material is placed in a sagger in a muffle furnace under an oxygen-containing air atmosphere with an oxygen partial pressure of 0.35 atm and a gas flow rate of 350 Nm 3 / h, firstly heat to 300℃ at a rate of 6℃ / min, keep warm for 2h; then heat to 550℃ at a rate of 6℃ / min, keep warm for 2h, then heat to 750℃ at a rate of 6℃ / min, keep warm for 2h, then heat to 920℃ at a rate of 4℃ / min, keep warm for 8h, complete sintering, and after cooling to room temperature with the furnace, grind or crush the obtained material to D50 of 5.5μm to obtain oxide Li 1.3 Ni 0.5 Co 0.2 Mn 0.25 Sb 0.05 O2.

[0113] Example 8

[0114] This embodiment provides an oxide LiNi 0.49 Co 0.2 Mn 0.3 La 0.01 O2, different from Example 1, weigh out 1.0% of polyvinyl alcohol (6.8g).

[0115] Comparative Example 1

[0116] Conventional LiNi 0.5 Co 0.2 Mn 0.3 O2 positive electrode material.

[0117] S1: Take Ni 0.5 Co 0.2 Mn 0.3 300g of (OH)2 precursor material and 124.2g of lithium carbonate were mixed by a small high-speed mixer. The mixed powder was put into a sagger and placed in a muffle furnace. Under the condition of oxygen-containing atmosphere, the partial pressure of oxygen was 0.35atm and the gas flow rate was 350Nm 3 / h, first heat to 300℃ at a rate of 6℃ / min, keep warm for 2h; then heat to 550℃ at a rate of 6℃ / min, keep warm for 8h, take samples for testing, then heat to 950℃ at a rate of 6℃ / min, keep warm for 8h, complete sintering; after cooling to room temperature with the furnace, the positive electrode material is obtained.

[0118] Comparative Example 2

[0119] Conventional LiNi 0.7 Co 0.1 Mn 0.2 O2 positive electrode material, using Ni 0.7 Co 0.1 Mn 0.2 (OH)2 is mixed with lithium hydroxide and then sintered. The preparation process is similar to that of comparative example 1. The insulation temperature is 820°C and the oxygen partial pressure in the oxygen-containing atmosphere is 0.45atm.

[0120] Comparative Example 3

[0121] Conventional LiNi 0.8 Co 0.1 Mn 0.1 O2 positive electrode material, using Ni 0.8 Co 0.1 Mn 0.1 (OH)2 is mixed with lithium hydroxide and then sintered. The main process is similar to that of comparative example 1. The insulation temperature is 750°C and the oxygen partial pressure in the oxygen-containing atmosphere is 0.95atm.

[0122] The test equipment or instruments of the present invention are shown in Table 4, wherein the test methods of the main instruments are as follows:

[0123] (1) Moisture and composition analysis The method in the national standard for lithium cobalt oxide (GB / T 20252-2014) was used, and the contents of all metal elements were determined by inductively coupled plasma optical emission spectrometry.

[0124] (2) XRD test conditions: Cu target Kα1, scanning rate 4° / min, 2θ range 10-80°.

[0125] The XRD patterns of materials at different temperatures were compared with the PDF standard card patterns and analyzed accordingly. The results are as follows: Figure 1 shown.

[0126] The XRD spectrum of the positive electrode material is compared with the PDF standard card spectrum and analyzed accordingly. The results are as follows Figure 1 As shown in Table 2.

[0127] (3) Sample SEM: The sample was prepared on carbon conductive glue and placed in the sample chamber of a scanning electron microscope. The voltage was set to 15KV and the current was set to 2.2A for observation. The results are as follows: Figure 2 , Figure 3 , Figure 4 and Figure 5 shown.

[0128] (4)DSC test: air atmosphere, heating rate 20℃ / min, 20℃~700℃, air flow 100ml / min, the results are as follows Figure 6 shown.

[0129] (5) Button performance test: The positive electrode materials prepared in Example 1 and Comparative Example 1 were used in lithium ion button batteries and charged and discharged at 4.4V 0.1C. The results are as follows: Figure 7 shown.

[0130] (6) Capacity / rate / cell swelling ratio test: The positive electrode materials prepared in Examples 1 to 8 and Comparative Examples 1 to 3 were used in lithium-ion batteries to test gram capacity, rate capability, and cell swelling ratio. The results are shown in Tables 2 and 3.

[0131] (7) Cycle performance test: The positive electrode materials prepared in Example 1 and Comparative Example 1 were used in lithium ion batteries and the charge and discharge cycle performance was tested at 4.5V 45°C 1C / 1C. The results are as follows: Figure 8 shown.

[0132] The raw materials or auxiliary materials of the present invention are shown in Table 5.

[0133] Table 1 Comparison of element composition test data of lithium-containing materials

[0134]

[0135] Table 2 Comparison of half peak width

[0136] Group 18.8° diffraction peak half-peak width Comparative Example 1-550℃ 0.423 Comparative Example 1-950℃ 0.145 Example 1 - 550°C 0.338 Example 1 - 920°C 0.132

[0137] Table 3 Rate performance data table at different voltages (4.2V, 4.35V, 4.4V)

[0138]

[0139] Table 44.4V high temperature storage (85℃ 4h) battery cell swelling data table

[0140]

[0141]

[0142] Table 5 Instrument and equipment information

[0143]

[0144] Table 6 Raw materials / auxiliary materials information

[0145]

[0146]

[0147] From the test results of lithium-containing materials in Table 1, it can be seen that the mass fraction of the Li element in the lithium-containing material is 1.04% to 4.68%, which is within the range of 0.5wt% to 8.4wt%; the mass fraction of (Ni+Co+Mn+A) is 27.2% to 37.5%, which is within the range of 21% to 61%; the mass fraction of the anion can be deducted from the mass fraction of the lithium element and the mass fraction of (Ni+Co+Mn+A) from 100%, and the mass fraction of the anion is 57.8% to 69.6%, which is within the range of 38% to 74%. In addition, in actual feeding, considering the loss of lithium element during sintering, the molar ratio of Li element to (Ni+Co+Mn+A) in the reactant will have an excess of 1% to 5% of Li element.

[0148] From Table 2 and Figure 1 It can be seen from the test results that in Example 1, the oxide material obtained when the sintering temperature is 550°C has formed a good crystal structure, while in Comparative Example 1, the positive electrode material obtained when the sintering temperature is 550°C fails to split at the diffraction peak around 38°, indicating that a good layered structure has not been formed, indicating that the diffusion resistance of lithium ions from the precursor in the lithium-containing material is small, and a good crystalline phase structure can be generated by reaction at a lower sintering temperature; further increasing the temperature, the XRD spectrum of the positive electrode material is obtained when the sintering temperature is increased to 920°C and 950°C in Example 1 and Comparative Example 1, wherein the spectrum of Comparative Example 1 is similar to the XRD spectrum of the oxide material obtained when the sintering temperature is 550°C in Example 1, indicating that after the lithium-free precursor in Comparative Example 1 is mixed with the lithium source, the lithium ions obtain sufficient diffusion power under high-temperature sintering conditions and react to generate a crystalline phase structure in the material.

[0149] In the XRD spectrum, the half-width of the diffraction peak of the tested material is used to illustrate the crystallization level of the material. Comparing the half-width of the 18.8° diffraction peak in the XRD spectrum of the positive electrode material obtained at different sintering temperatures in Comparative Example 1 and Example 1 (see Table 1), at a sintering temperature of 550°C, the half-width of the oxide material in Example 1 (0.338) is much smaller than the half-width (0.423) of the positive electrode material in Comparative Example 1, indicating that the oxide material (Example 1) obtained at a lower sintering temperature of 550°C has a better crystal structure than Comparative Example 1. The half-width (0.145) of the conventional precursor after mixing with the lithium source (i.e., Comparative Example 1) at a higher sintering temperature (such as 950°C) is larger than that of Example 1 after sintering at 920°C (0.132). It shows that the diffusion resistance of the lithium element is reduced by preparing the lithium-containing material in the present invention, and a solid phase reaction can occur at a lower sintering temperature to generate an oxide material with a better layered structure. Conventional precursors and lithium sources need to be mixed at a higher sintering temperature to promote the diffusion of lithium from the surface of the precursor to the inside, and finally generate a layered positive electrode material. Figure 2 , Figure 3 , Figure 4 and Figure 5 It can be seen from the test results that Example 1 has formed single crystal grains of 3-5 μm in size with clear grain boundaries at a sintering temperature of 550°C; while Comparative Example 1 failed to form complete grains at a sintering temperature of 550°C, and only formed grains of 1-2 μm in size at a sintering temperature of 950°C; This indicates that the reaction activity of Example 1 is stronger than that of Comparative Example 1, and the diffusion of Li elements can be completed to form grains at a lower temperature, that is, the present invention reduces the sintering temperature of the material.

[0150] from Figure 6 It can be seen from the test results that the thermal change peak of Example 1 is at 200-300°C, and the thermal change peak of the comparative example is at 350-550°C, that is, Example 1 starts the chemical reaction at around 300°C, and Comparative Example 1 starts the chemical reaction at around 500°C. Example 1 has higher chemical activity than Comparative Example 1.

[0151] from Figure 7 There is no obvious difference in the 4.4V 0.1C charge-discharge curves between the oxide material in Example 1 and the positive electrode material in Comparative Example 1, indicating that the oxide material obtained by the present invention and the positive electrode material prepared by the conventional method have similar capacity performance.

[0152] Under high temperature and high voltage cycle test conditions, only positive electrode materials with more stable structures can maintain a better cycle life. Figure 8The test results shown in the figure show that when a high-temperature cycle test is carried out at 4.45V and 45°C, the cycle stability of the oxide material obtained by the present invention is better than that of the positive electrode material prepared by the traditional method, indicating that the oxide material prepared by the lithium-containing material proposed in the present invention has a better structural stability than the positive electrode material prepared by the traditional method.

[0153] It can be seen from the test results in Table 3 that the rate performance of Examples 1 to 8 is all above 90%, and the rate performance is improved by ≥3 percentage points compared with Comparative Examples 1 to 3. In particular, the comparison between Examples 1 to 3 and Example 8 and Comparative Example 1 shows that the rate performance of the oxide provided by the present invention is better than that of the positive electrode material prepared by the traditional method.

[0154] In addition, the stability of the material structure can also be explained by the high-temperature storage swelling behavior of the battery cell, which is based on the fact that the side reaction between the electrode material and the electrolyte in the charging state is sensitive to temperature, and the material with a stable structure has a small side reaction with the electrolyte in the charging state, produces less gas, and has a small swelling of the battery cell. From the test results of high-temperature storage of the embodiments and comparative examples (see Table 4), it can be seen that under the conditions of 4.4V 85℃ storage for 4h, the swelling rate of the battery cells of Examples 1-8 is ≤5%, and the swelling rate of the battery cells of Comparative Examples 1-3 is ≥7%. The high-temperature storage swelling rate of the battery cells of the comparative examples is higher than that of the embodiments, which indirectly shows that the oxide provided by the present invention has better structural stability than the positive electrode material prepared by the traditional method.

[0155] In summary, the oxide material of the present invention is prepared by lithium-containing materials, and the lithium-containing materials used are mixed at the atomic level by adding lithium elements during the preparation stage, so as to reduce the batching and mixing process, improve the consistency of product batches, production efficiency and cost savings. Compared with the traditional process, the oxide material of the present invention can be prepared at a lower temperature, saving energy. Compared with the positive electrode material prepared by the traditional process, since the lithium element and the nickel, cobalt and manganese elements in the lithium-containing material are evenly distributed, the oxide material prepared by the present invention has better structural stability, and in the high limiting voltage system, the 2C / 0.2C rate performance is excellent, and the rate performance improvement rate is ≥3% compared with the comparative example, and the battery cell swelling rate is <5% during high temperature storage; the prepared battery cell has excellent high temperature cycle performance, and the cycle life is increased from 300cycle@80% to ≥800Cycle@80% under the test conditions of 4.5V 45℃1C / 1C, with an increase of about 166%.

[0156] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. An oxide material, characterized in that: The chemical formula of the oxide material is Li m Ni a Co b Mn c A (1-a-b-c) O2; where 0.9≤m≤1.3, 0≤a≤1, 0≤b≤1, 0≤c≤1, 0< a+b+c≤1, A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn; the mass fraction of lithium element in the oxide material is 6.45% to 9.36%, and the total mass fraction of nickel element, cobalt element, and manganese element is 50% to 60%.

2. The oxide material according to claim 1, characterized in that The D50 median particle size of the oxide material is 1.5 to 20 μm, and the BET is 0.2 to 1.8 m2 / g.

3. The oxide material according to claim 1-2, characterized in that: The oxide material is made of a lithium-containing material, which can be made by directly sintering the lithium-containing material or by mixing the lithium-containing material with an appropriate amount of lithium source and then sintering it; the lithium-containing material has a molecular formula of Li n Ni x Co y Mn z A (1-x-y-z) P, P is CO3 2- 、OH-、C2O4 2- , O 2- 、CH3COO - One or more of the following: wherein 0.1≤n≤1.3, 0≤x≤1, 0≤y≤1, 0≤z≤1, 0<x+y+z≤1, and A comprises at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn; and the sintering method comprises placing the lithium-containing material or a mixture of the lithium-containing material and a lithium source in a muffle furnace, heating the temperature to 500-1000° C. at a heating rate of 1-8° C. / min, sintering for 5-20 hours under an oxygen-containing atmosphere, and naturally cooling the material to obtain the oxide material.

4. The lithium-containing material according to claim 3, characterized in that The mass fraction of Li element in the lithium-containing material is 0.5% to 8.4%, the mass fraction of (Ni+Co+Mn+A) is 21% to 61%, and the mass fraction of P is 38% to 74%, wherein A includes at least one of Fe, Ti, Al, Mg, Nb, Ce, Sb, Y, La, Zr, and Zn.

5. The lithium-containing material according to claim 3, characterized in that: The median particle size D50 of the lithium-containing material is 1.5 to 25 μm.

6. The lithium-containing material according to claim 3, characterized in that The lithium-containing material is heated at 500-600°C in an oxygen-containing atmosphere (oxygen partial pressure ≥ 0.21 atm) with an atmosphere flow rate of 100-700 Nm 3 / h, sintered for 2 to 10 hours, and in the XRD spectrum of the obtained product under the test conditions of Cu target Kα1, scanning rate 4° / min, and 2θ range of 10 to 80°, the half-peak width of the diffraction peak 18.5-19.0° is 0.100 to 0.

380.

7. The lithium-containing material according to claim 3, characterized in that The DSC spectrum of the lithium-containing material has at least two endothermic peaks between 100° C. and 350° C.

8. The lithium-containing material according to claim 3, characterized in that The preparation method can be a solid phase method, a liquid phase method or a solid-liquid mixing method, preferably a liquid phase method or a solid-liquid mixing method.

9. A positive electrode sheet, characterized in that: The oxide material according to any one of claims 1 to 2 has a compacted density of 3.2 to 4.2 g / cc.

10. A lithium ion battery, characterized in that: The positive electrode sheet according to claim 9 is included; in the cut-off voltage range of 4.2 to 4.6 V, the 2C / 0.2C rate performance is improved by ≥3% over the battery cell prepared by the positive electrode material prepared by the conventional method, and the swelling rate of the high-temperature storage battery cell is ≤5%.

Citation Information

Cited By

  • Lithium supplement dispersing agent and preparation method thereof, positive electrode slurry and secondary battery

    CN120600820A